Brand personality to enhance loyalty in sports services: the role of congruence - Alguacil, M.; Parra-Camacho, D.; Mundina, C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
This research aims to test whether and to what extent brand personality has an influence on the user’s increased levels of consistency or identification with the brand. Likewise, it seeks to know whether such congruence is a determining element for achieving the loyalty of users of sports services. To this end, a measuring instrument based on existing literature has been used to analyse both the reliability and validity of the instrument and the relationships between the variables proposed with the smartPLS structural equation programme. The results indicate that the sincerity, competence and sophistication dimensions of brand personality significantly influence the improvement of congruence and explain up to 55% of its variance, as well as congruence alone is capable of explaining up to 52% of the variance of loyalty.